RELATIONSHIP BETWEEN CLIMATE VARIABLES AND DENGUE INCIDENCE IN WEST INDONESIA - Ahmad Ghiffari; Ratika Febriani; Galuh Pratama Mynanda; Thia Prameswarie (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2024)
Background: Dengue fever is a major public health problem, especially in heavily populated metropolitan areas like Palembang City, Indonesia. Gaining insight into the impact of climatic conditions on the dynamics of dengue transmission is essential for guiding specific public health actions. Objective: The objective of this study is to examine the correlation between temperature, rainfall, wind speed, air humidity, and the occurrence of dengue disease in Palembang City. Methods: Using observational data collected from 2016 to 2019 and 2022, we applied bivariate analytic approaches to evaluate the associations between meteorological factors and the incidence of dengue disease. Results: The findings demonstrate a notable inverse relationship between temperature and the occurrence of dengue disease, although rainfall displayed a favorable relationship. The relationships between wind speed, air humidity, air pressure, and dengue fever incidence were shown to be weaker. Conclusion: These findings highlight the significance of utilizing meteorological factors in early warning systems to enhance disease surveillance and control measures in metropolitan environments. This work helps to the creation of evidence-based strategies for reducing the burden of dengue fever in locations where it is common by explaining the intricate connections between climatic conditions and the dynamics of dengue transmission.